Fungsi Dinas Lingkungan Hidup Kabupaten Sikka dalam Pengelolaan Sampah di Kota Maumere (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
The aim of this research is to determine the regulation of the function of the Sikka Regency Environmental Service in waste management in Maumere City and the participation of the Maumere City community in waste management. In order to answer this research, an analysis of the relationship between laws governing waste management and Sikka Regency regional regulations governing waste management was carried out, especially the regulation of the Sikka Regency Environmental Service's function in waste management. The type of research used by the author is Empirical Normative Legal research. The data sources in this research are primary and secondary data sources. Analysis of data and legal materials in this research uses qualitative analysis in accordance with primary data and secondary data obtained from the research results. Based on the research results, the two existing regional legal products, namely Sikka Regency Regional Regulation Number 16 of 2016 and Sikka Regent Regulation Number 42 of 2021, regulate the function of the Sikka Regency Environmental Service in waste management in Maumere City. with what has been regulated in Law Number 18 of 2008 concerning Waste Management as the highest law. The weakness of the existing regulations, both laws and regional regulations, is law enforcement. The participation of the people of Maumere City in management is that the people sort out waste that can still be used for reuse so that it is not just thrown away. Apart from that, the community also proposed a program at the Environmental Service for waste management so that waste handling in Maumere City can run well.